El cine ecuatoriano en las ediciones de los Premios Colibrí y los nuevos proyectos audiovisuales - Coello Coello, Juan Pablo (2021)
The present case research, commits to an analysis of the audiovisual projects presented in the editions of the Colibri Awards, of which each edition was analyzed to know the trend in new audiovisual projects, the research will be a qualitative method in which it will have interview and observation sheet, from which it was possible to know, the entities responsible for making the aforementioned award, the purpose they have in making the Colibri Awards, also the processes to be followed by the participating audiovisual projects and how difficult was the situation in the third edition of the Colibri Awards. The analysis of each edition will be the tool to describe in detail the development of local films, according to the different versions of the Colibri Awards, in the observed editions different results will be obtained, such as the genre with the highest number of nominations and the year in which the most audiovisual projects were released, The similarity that this research seeks to achieve is to encourage the establishment of a participatory society in this field, ensuring opportunities for the Ecuadorian community, especially future producers, directors and actors, thus highlighting the richness of Ecuador's film history.